(untitled) (EU and comparative law issues and challenges series (ECLIC), 2024)
In the context of the key efforts and objectives of the European Green Deal, which represents a transformative agenda, aiming for climate neutrality by 2050 while promoting sustainable economic development across the European Union (EU), this paper aims to analyze competition policy as a fundamental tool to support green innovation, regulate state aid and balance market dynamics in renewable energy and other green sectors. This paper analyses, among other things, the legal frameworks and the interaction between competition policy and EGD, taking into consideration market approaches and strategies, which are being adapted to promote sustainability. By integrating environmental objectives into traditional competition principles – such as efficiency, consumer welfare and market access – the EU seeks to mitigate anti-competitive practices while fostering innovation in green technologies. Through case studies and policy analysis, this paper examines the role of competition policy in addressing key challenges, including market concentration, state aid for green investments and regulatory coherence. This analysis contributes to the development of the discourse on EU competition law and its alignment with sustainability, providing insights into the possibilities and limitations of this integration in achieving long-term climate and economic goals.